Bromide Induced Room‐Temperature Formation of Photoactive Formamidinium‐Based Perovskite for High‐Efficiency, Low‐Cost Solar Cells. Issue 4 (5th December 2018) - Lv, Xinding; Dong, Xuemei; Ye, Zhili; Zhou, Junshuai; Deng, Fei; Zheng, Yan‐Zhen; Tao, Xia
Abstract : State‐of‐the art perovskite solar cells (PSCs) are obtained by using a high‐crystalline and uniform morphological perovskite film that usually requires a thermal procedure to induce its crystallization. Room temperature processing photoactive perovskite film represents a feasible approach to break through the technology barrier arising from high temperature annealing procedures; however, the photovoltaic performance of fabricated PSCs varies significantly in most routine laboratories with ambient temperature altering. Herein, the authors report for the first time that highly photoactive black phase FA‐based perovskite films with high performance and reproducibility can be room temperature processed via the Br induced crystallization effect. It is found that Br adding content varies as a function of ambient temperature fluctuation from 35–40 to 20–25 °C. The halide Br/I formulation are 0.2/2.8 and 0.5/2.5 for room‐temperature perovskite crystallization in ambient temperatures of 35–40 and 20‐25 °C, yieldings solar to electric power conversion efficiency of 19.59 and 17.53% with high reproducibility, respectively. This efficiency (19.59%) is comparable to the best‐performing PSCs based on thermal processing perovskite films. This work provides a valuable and practical guide to room‐temperature fabrication of PSCs with high efficiency and reproducibility by delicate control of halide anions. Abstract : Br induced room temperature crystallization of highly photoactive black phase FA‐based perovskite films with high performance and reproducibility is reported. The halide Br/I formulation are 0.2/2.8 and 0.5/2.5 for room‐temperature perovskite crystallization at 35–40 °C and 20–25 °C, yielding solar to electric conversion efficiency of 19.59 and 17.53% with high reproducibility, respectively.